Cytotoxic clerodane diterpenoids from Croton crassifolius. Issue 5 (1st March 2017) - Tian, Jin-Long; Yao, Guo-Dong; Wang, Yu-Xi; Gao, Pin-Yi; Wang, Di; Li, Ling-Zhi; Lin, Bin; Huang, Xiao-Xiao; Song, Shao-Jiang
Graphical abstract: Abstract: Hepatocellular carcinoma (HCC) is the most common type of liver cancer, and treatment options for HCC are limited. In addition, the discovery of new natural compounds with anti-hepatocarcinoma activity is attracting increasing attention. For this reason, phytochemical investigation of Croton crassifolius led to the isolation of 17 diterpenoids, including three new clerodane diterpenoids, named crassifolius A-C (1 –3 ), along with 14 known ones (4 –17 ). Their structures were established by 1D, 2D NMR, HR-ESI-MS, detailed calculated electronic circular dichroism (ECD) spectra and the assistance of quantum chemical predictions (QCP) of 13 C NMR chemical shifts. The cytotoxicities of all these compounds against human liver cancer lines (HepG2 and Hep3B) were determined. Among them, compound1 exhibited good cytotoxicity with IC50 value of 17.91 μM against human liver tumor cells Hep3B. Following further studies of the anti-tumor mechanism of compound1 -induced cell growth inhibition, we found that compound1 caused apoptotic cell death in Hep3B cells by detecting morphologic changes and Western blotting analysis.